Admission of Non-Traditional Students in the 21st Century Universities: A Tradition of Transformations - Lwanga, Jordan Byekwaso; Ngaka, Willy; Openjuru, George Ladaah (East African Journal of Education Studies, 2025)
This article analyzes the transformations in the organization and governance of admissions for older adults (non-traditional students – NTSs) in higher education at one of the public universities in Uganda. Adulthood demands acquiring new coping strategies and skills to adapt to the requirements of new and emerging roles. This demand goes beyond depending on introductory training and informal experiences based on cultural wisdom. A growing belief underscores HE as a critical tool in responding to these demands. To champion this belief, many universities are contextually defining and implementing admission decisions to select deserving adults to enrol for university education. We collected qualitative data from university managers (some of whom doubled as academics), mature age coaches, and graduate and continuing non-traditional students. The purpose of this article was to analyze how institutional decisions on the admission of non-traditional students have evolved and their implications on the future development of the HE sector. This article illustrates and concludes by raising awareness among current and future sector managers and scholars who might be new to NTSs on how institutional decisions leading to their enrolment emerged and their implications for future practice